The CPTM way : the smart partnership way (Commonwealth Partnership for Technology Management Ltd (CPTM) LondonGB, 2014)
Presents an account of the special approaches CPTM has created for contributing to the development and transformation of emerging economies in the Commonwealth and beyond.
Keywords: PARTNERSHIP